2017
DOI: 10.22467/jwmr.2017.00171
|View full text |Cite
|
Sign up to set email alerts
|

Vaccum-Assisted Closure Therapy in Split-Thickness Skin Graft on the Wound on the Contours of the Body

Abstract: Through investigation of the recording, the testing group included 106 patients, who

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Pyo et al . also observed better patient satisfaction which was as a result of the increased mobility after negative pressure dressing and the perceived increased effectiveness of the medical team due to the greater ease of dressing application compared to the conventional method [ 15 ]. It has also been noted that patients were more comfortable with less need for dressing change, lower cost of nursing care and less risk of cross infection [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pyo et al . also observed better patient satisfaction which was as a result of the increased mobility after negative pressure dressing and the perceived increased effectiveness of the medical team due to the greater ease of dressing application compared to the conventional method [ 15 ]. It has also been noted that patients were more comfortable with less need for dressing change, lower cost of nursing care and less risk of cross infection [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients and medical staff have satisfactory results due to increased mobility during hospitalization. 34 Blackburn et al and Argenta et al found that it is a useful than bolster dressing in sites which are difficult. 6,35 Argenta et al also reported that there is better and faster engraftment of Integra over exposed tendon, bone, joint, and bowel with use of VAC.…”
Section: Graft Uptakementioning
confidence: 99%
“…Una vez aceptado su uso, por ejemplo, en el tratamiento de quemados, fascitis necrosante, (1) infecciones, (2) etc, uno de los pasos lógicos era utilizarla como sellado, protección y acelerante en el prendimiento de los injertos cutáneos, hecho que venimos realizando en nuestro Servicio desde hace más de 10 años. (1) Por eso no me extraña que su grupo haya pensado en cómo cuantificar, de la manera más objetiva y científica posible, el grado de prendimiento de los mismos, y además haciéndolo con unos recursos relativamente sencillos.…”
Section: Estimados Autoresunclassified
“…Es importante que el cizallamiento entre el injerto y el lecho receptor no se presente, por este motivo se debe garantizar la adherencia del injerto al lecho receptor durante los primeros 5 días, ya que este es el periodo más importante para la nutrición e integración del injerto de piel. (2) El tipo de curación oclusiva más frecuentemente utilizado se realiza colocando un apósito humectado con algún tipo de petrolato sobre el injerto cubierto con un apósito y vendaje con algo de presión sobre el área receptora, con el objetivo de que el injerto se adhiera al lecho receptor y permanezca fijo y aislado del medio externo. Este tipo de curación es conocida como apósito de Blair-Brown.…”
Section: Introductionunclassified